A NOTE ON SEMI-OPEN SETS IN TRICLOSURE SPACES (2020)
In this paper, we used the notion of triclosure spaces to introduce and study the concept of semi-open set in triclosure spaces. Besides, we show some of their properties. Moreover, the notions of semi-continuous and semi-irresolute functions in a triclosure spaces are studied. Furthermore, we prove some of their properties.